Interface engineering of porous nickel-iron phosphates with enriched oxygen vacancies as an efficient bifunctional electrocatalyst for high current water splitting. (1st March 2023) - Wang, Lixia; Yu, Hongbo; Huang, Zhiyang; Luo, Zuyang; Isimja, Tayirjan Taylor; Xu, Shoulei; Yang, Xiulin
Highlights: A novel nickel-iron phosphates is fabricated by a controllable two steps. The catalyst has a sheet-like structure and abundant oxygen vacancies. The bifunctional catalysts exhibit good overall water splitting performance. Strong electron interactions and rich oxygen vacancies are the key to improve performance. Abstract: The delicate design of non-precious metal-based bifunctional electrocatalysts for simultaneous oxygen/hydrogen evolution reactions is pivotal for developing green and sustainable energy sources. Here, we have fabricated a novel nickel-iron phosphate heterostructure with abundant oxygen vacancies (Fe0.86 Ni0.14 -POx /CC) via hydrothermal reaction and gas-phase phosphating treatment. By appropriately adjusting the ratio of Ni/Fe, the electronic structure is regulated, thereby optimizing the oxygen vacancies to form abounded electrocatalytic active centers on the catalyst surface. The obtained Fe0.86 Ni0.14 -POx /CC catalyst reveals low overpotentials of 247 and 125 mV for OER and HER at a current density of 10 mA cm −2, respectively. Besides, the overall water splitting electrolyzer originated from Fe0.86 Ni0.14 -POx /CC only requires a cell voltage of 2.01 V to deliver a current density of 500 mA cm –2 with good stability of 100 h (10 mA cm −2 ). Importantly, Fe0.86 Ni0.14 -POx /CC possess 96.9 and 97.7% Faradaic yield for the generation of H2 and O2, respectively. This work invokes new feasibility for developing robust and cost-effective phosphate catalysts for electrochemical overall water splitting. Graphical abstract: A novel nickel-iron phosphates with abundant oxygen vacancies of Fe0.86 Ni0.14 -POx /CC catalyst was successfully constructed by hydrothermal reaction and gas-phase phosphating treatment. The bifunctional catalyst exhibits good HER and OER performance for overall water splitting in alkaline solution. The satisfactory electrocatalytic performance is mainly attributed to the unique sheet-like morphology that exposes more active sites, as well as the strong electronic interaction and abundant oxygen vacancies that change the intrinsic activity and enhance the reaction kinetics. Image, graphical abstract